Onchocerca volvulus as a risk factor for developing epilepsy in onchocerciasis endemic regions in the Democratic Republic of Congo: a case control study - Michel Mandro; Patrick Suykerbuyk; Floribert Tepage; Degratias Rossy; Francoise Ngave; Mirza Nazmul Hasan; An Hotterbeekx; Germain Mambandu; Jean Marie Kashama; Anne Laudisoit; Robert Colebunders (BMC, 2018)
Abstract Background A high prevalence of epilepsy has been observed in onchocerciasis endemic areas in the Democratic Republic of Congo (DRC). With this study we aimed to investigate whether Onchocerca volvulus infection is a risk factor for developing epilepsy in onchocerciasis endemic regions in the DRC. Methods Between October and December 2015, a multi-centre case control study was performed in onchocerciasis endemic health zones (HZ) in the DRC: one study site was situated in Tshopo Province in the HZ of Wanierukula (village of Salambongo) where there had been 13 annual community distributions of treatment with ivermectin (CDTI), a second was situated in Ituri Province in the HZ of Logo (village of Draju) where ivermectin had never been distributed and in the HZ of Rethy (village of Rassia) where there had been THREE CDTI annual campaigns before the study. Individuals with unprovoked convulsive epilepsy of unknown etiology were enrolled as cases (n = 175). Randomly selected healthy members of families without epilepsy cases from the same village and age-groups and were recruited as controls (n = 170). Results Onchocerciasis associated symptoms (e.g., itching and abnormal skin) were more often present in cases compared to controls (respectively, OR = 2.63, 95% CI: 1.63-4.23, P <  0.0001 and OR = 3.23, 95% CI: 1.48-7.09, P = 0.0034). A higher number of cases was found to present with microfilariae in skin snips and with O. volvulus IgG4 antibodies in the blood compared to controls. Moreover, the microfilariae load in skin snips was 3-10 times higher in cases than controls. Conclusions This case control study confirms that O. volvulus is a risk factor for developing epilepsy in onchocerciasis endemic regions in the DRC.